Tuning Parameter Kontrol Proporsional–Integral Menggunakan Sugeno Fuzzy Inference System - Wahyudi Wahyudi; Iwan Setiawan; Eduward Tigor (Transmisi: Jurnal Ilmiah Teknik Elektro, 2012)
PI (Proportional-Interal) controller is a control method that have been applying in industrial proccess. This control  method have two control parameters the proporsional parameter (Kp) and the integral parameter (Ki). In conventional methot, parameter PI is tuned by using trial and error. That problem is how tuning parameter is easyly and not long time to find this parameter. Autotuning paramer by  using fuzzy logic is one method to solve this problem. In autotuning method, PI parameter is calculate by some of rules base. This methode have two inputs, error and change of error. Main controller of this plant, control fluid level, use Atmega8535 microcontroller and water pump as the actuator to control. This reseach is succesfull for  tuning PI parameter and to control the fluid level as we want. The respon system have rapid rise time, no offset and no overshoot. The respon system is stable although we add some noise in the system.Keywords: PI (Proportional-Integral), autotuning fuzzy, and ATmega 8535 microcontroller